Integrated Analysis of lncRNA and circRNA Mediated ceRNA Regulatory Networks in Skin Reveals Innate Immunity Differences Between Wild-Type and Yellow Mutant Rainbow Trout (Oncorhynchus mykiss) - Wu, Shenji; Huang, Jinqiang; Li, Yongjuan; Liu, Zhe; Zhao, Lu (Frontiers in Immunology, 2022)
Fish skin is a vital immune organ that forms the first protective barrier preventing entry of external pathogens. Rainbow trout is an important aquaculture fish species that is farmed worldwide. However, our knowledge of innate immunity differences between wild-type (WR_S) and yellow mutant rainbow trout (YR_S) remains limited. In this study, we performed whole transcriptome analysis of skin from WR_S and YR_S cultured in a natural flowing water pond. A total of 2448 mRNAs, 1630 lncRNAs, 22 circRNAs and 50 miRNAs were found to be differentially expressed (DE). Among these DEmRNAs, numerous key immune-related genes, including ifih1, dhx58, trim25, atp6v1e1, tap1, tap2, cd209, hsp90a.1, nlrp3, nlrc3, and several other genes associated with metabolism (gstp1, nampt, naprt and cd38) were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses of DEmRNAs revealed that many were significantly enriched in innate immune-related GO terms and pathways, including NAD+ADP-ribosyltransferase activity, complement binding, immune response and response to bacterium GO terms, and RIG-I-like receptor signaling, NOD-like receptor signaling and phagosome KEGG pathways. Furthermore, the immune-related competing endogenous RNA networks were constructed, from which we found that lncRNAs MSTRG.11484.2, MSTRG.32014.1 and MSTRG.29012.1 regulated at least three immune-related genes (ifih1, dhx58 and irf3) through PC-5p-43254_34, PC-3p-28352_70 and bta-miR-11987_L-1R-1_1ss8TA, and tap2 was regulated by two circRNAs (circRNA5279 and circRNA5277) by oni-mir-124a-2-p5_1ss13GA. The findings expand our understanding of the innate immune system of rainbow trout, and lay the foundation for further study of immune mechanisms and disease resistance breeding.